Sifat Pengeringan Alami Kayu Tumeh (Combretocarpus rotundatus Dans) pada Radial Di Kalimantan Tengah : Natural Drying Properties Radial Direction of Tumeh (Combretocarpus rotundatus Dans) In Central Kalimantan - Supriyati, Wahyu; Alpian, Alpian; Yanciluk, Yanciluk; Andi, Andi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The use of wood requires wood conditions with low air content (KA) according to the environment. Its position can influence wood properties in the trunk. The objectives of this research are a) to analyze the natural drying properties, namely the drying rate in the radial direction of tumeh wood, and b) to analyze natural drying defects. The method used refers to Hidayat and Karnasudirdja 1987. The parameters measured are natural drying properties (drying rate) and drying defects. Statistical analysis used t test. The results show that the natural drying rate pattern is greater near the liver than near the bark. The location in the radial direction of the wood (near the bark and the heart) has no significant effect to the natural drying of tumeh wood. The natural drying defect found were surface check and end check. Further research into the natural drying properties of tumeh wood in different diameters is necessary to utilize the wood effectively and efficiently.